Théorie de la régulation et histoire du droit :un croisement fertile - Samuel Klebaner (Revue de la Régulation)
The aim of this article is to explore the possible connections between the methods used by scholars in the research domain of the Legal History and the research agenda of the French Régulation Theory (TR). The TR is a heterodox economic approach which aims to analyze the economic dynamics through the studies of the institutions’ stabilization and crises. This field is at the crossroad between different social sciences. The crossing between the different research domains enables the stabilization of methods and concepts and to go beyond the limits of theories. The methodologies developed in the Max Planck Institute of Frankfurt am Main (MPIeR) analyze the emergence and the performativity of law. The originality of this method lies in its attempt to reduce the place of the State in the dynamic of legal institutions, through a constructivist approach of the studied spaces of regulation. In developing concepts like multinormativity, governance, science of regulation and law as communication, we show how the research of this school can both inspired the RT in exploring new dimensions, or in going beyond the State-centered approach of institutional dynamics.